Evaluation Of Free Activity Lesson Based On The Opinions Of Teachers Working In Multigrade Clasrooms (Sample Of Elazig) - Kazu, Hilal; Aslan, Serkan (Dergipark Akad, 2013)
The aim of this study is to determine the teachers' working in multigrade clasrooms views on free activity lesson. Qualitative research design has been used in the research. A total of 35 multigrade clasroom teachers working in the Karakocan and Sivrice districts of Elazig have participated in this study. The data of the research have been collected by interview form comprised of open-ended questions. The activity has been formed around the categories of ''planning of free activity lesson'', ''activities applied in free activity lesson'' and ''problems encountered in free activity lesson and recommendations'' in relation to free activity lesson. Content analysis and descriptive analysis have been used in the analysis of the data. According to the findings; it has used that already-planned lesson plans while planning the free-activity classes, they work to correct deficiencies of other subjects in this lesson, they have had problems due to the absence of the teacher guide book. The participants have developed solutions to similar problems which are encountered in free activity lesson. Finally, recommendations such as a teachers' manual for the free-activities class should be developed, attention should be paid on providing necessary materials for free-activities classes, gymnasiums, art and activity centers aimed for common use of teachers and students in these schools should be created have been made on the basis of the findings of research results.
Keywords: Multigrade classroom; free activity lesson; teacher opinions